Improved preparation of 4(5)-aryl-2-(β-d-glucopyranosyl)-imidazoles, the most efficient glucose analogue inhibitors of glycogen phosphorylase. Issue 97 (4th October 2016) - Szennyes, Eszter; Bokor, Éva; Batta, Gyula; Docsa, Tibor; Gergely, Pál; Somsák, László
Abstract : Large scale (up to 20 g) preparation ofI andII allowed the best inhibitors of glycogen phosphorylaseIII to be synthesized in close to 60% overall yields fromI . Abstract : The synthesis of 4(5)-aryl-2-(β-d -glucopyranosyl)-imidazoles, the currently most efficient glucose derived inhibitors of glycogen phosphorylase enzymes was amended and extended by using O -perbenzylated β-d -glucopyranosyl cyanide as the starting material. This compound and its derivatives C -(β-d -glucopyranosyl)formimidate and formamidine were obtained in large scale reactions to give the products in ∼20 grams amounts. Ring closing reactions of the formimidate and formamidine by α-amino- and α-bromoketones, respectively, produced the O -perbenzylated imidazoles which were deprotected by catalytic hydrogenation or by EtSH/BF3 ·OEt2 . Newly prepared 4(5)-(4-nitro- and -aminophenyl)-2-(β-d -glucopyranosyl)-imidazoles proved less efficient inhibitors ( K i values of 1141 and 411 nM, respectively) than their unsubstituted counterpart ( K i = 280 nM).